Al-Tasamuh al-Diniy 'inda Yusuf al-Qardhawiy - Zulkifli Reza Fahmi (Journal of Comparative Study of Religions (JCSR), 2021)
This paper aims to examine the concept of religious tolerance from Yusuf al-‎Qardhawi's perspective. The descriptive-analytical method is used to describe and analyze the thoughts of Yusuf al-Qardhawi and his relationship with the thoughts of other Muslim scholars. From this research it was found; first, religious tolerance according to Yusuf al-Qardhawi is to give non-Muslims the freedom to choose their religion and not to force them in any form. Second, "the starting point of religious tolerance is freedom of religion, unity of the people, justice and muâmalah with non-Muslims. Third, freedom of religion is based on the view that differences are the will of God and that humans cannot force themselves to make all human beings believe. Fourth, there are some things that are allowed for Muslims to be tolerant towards non-Muslims but there are also things that are not allowed at all, such as recognizing the truth of the teachings of other religions and participating in the worship of other religions. Although al-Qardhawi is a great scholar, his thoughts are still criticized, so the study of his thoughts is interesting to discuss.